2018
DOI: 10.1029/2017jd027952
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Rural and Suburban Sources of Urban Haze Formation in China: A Case Study From the Pearl River Delta Region

Abstract: Although particulate matter (PM)‐driven haze is a common phenomenon in many Chinese cities, studies on the sources of its key components, such as organic carbon (OC) and elemental carbon (EC), are poorly constrained. In this study, PM with aerodynamic diameters less than 10 (PM10), 2.5 (PM2.5), and 1 μm (PM1) were collected at an urban site in the core city of the Pearl River Delta region in summer 2013. The average PM10, PM2.5, and PM1 mass concentrations were 109 ± 28.4, 57.7 ± 15.0, and 50.9 ± 13.2 μg/m3, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 74 publications
(159 reference statements)
3
27
0
Order By: Relevance
“…Table 3 lists the 14 C results from PM 2.5 in three cities during 2012-2014 published in previous studies. Compared with previous studies, the seasonal variations of carbon sources in the three cities were highly consistent with previous observations conducted in different seasons (Liu et al, 2014(Liu et al, , 2016Liu et al, 2017c;Liu et al, 2018). The carbon sources from OC and EC of high-PM 2.5 samples and low-PM 2.5 samples from each season were nearly consistent in this study (Fig.…”
Section: Seasonal Variation Of 14 C Contentsupporting
confidence: 90%
See 3 more Smart Citations
“…Table 3 lists the 14 C results from PM 2.5 in three cities during 2012-2014 published in previous studies. Compared with previous studies, the seasonal variations of carbon sources in the three cities were highly consistent with previous observations conducted in different seasons (Liu et al, 2014(Liu et al, , 2016Liu et al, 2017c;Liu et al, 2018). The carbon sources from OC and EC of high-PM 2.5 samples and low-PM 2.5 samples from each season were nearly consistent in this study (Fig.…”
Section: Seasonal Variation Of 14 C Contentsupporting
confidence: 90%
“…Due to the limited data, these results might not reflect the true source variation over a 1-year period. For example, carbon source dynamics of carbonaceous aerosols during haze formation in Guangzhou indicated that there are significant differences in the carbon sources of high-PM 2.5 samples and low-PM 2.5 samples during spring and summer (Liu et al, 2016(Liu et al, , 2018. In addition, carbon sources of the high-PM 2.5 samples in Guangzhou winter also differ from each other (Liu et al, 2014).…”
Section: Seasonal Variation Of 14 C Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the accumulation of traffic emissions has frequently been reported as a primary cause of pollution events in urban areas of the PRD (Qin et al 2017). In contrast, biomass burning, which is extremely rare at most times of the year, nonetheless plays more important roles in particle concentrations and pollution events in the PRD in harvest season (Zhang et al 2010;Tao et al 2014;Wang et al 2016;Liu et al 2018;Zhou et al 2018). Influenced by multiple atmospheric conditions such as relative humidity and temperature, secondary processes, mainly generating sulfates, nitrates, and secondary organic aerosols, also substantially contribute to ambient aerosol concentrations (Hua et al 2015;.…”
Section: Introductionmentioning
confidence: 99%